No country for old men: on mentoring in medicine, by David Loxterkamp. (18th December 2017) - Loxterkamp, David
Abstract : For medicine to retain its ethical foundation and dedication to service, people at the end of their careers must pass the torch to those at the beginning, writes David Loxterkamp